Neutralność opodatkowania dochodu w aspekcie decyzji inwestycyjnych przedsiębiorstw - Adamczyk, Adam (Neutrality of Income Taxation in the Aspect of Corporate Investment Decisions, 2007)
The aim of the article was to examine if Polish corporate income taxation is neutral for corporate investment decisions. The problem was analyzed on the base of the NPV model. Simulations that were conducted using this model proved that corporate income taxation in Poland can affect as well absolute and relative investment decisions. The investigation also showed that influence of taxation can be eliminated by accepting the model of corporate income tax which was proposed by R.E. Hall and A. Rabushka.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 15-25